Luminescence of oxygen activated LiF crystals induced with pulsed beam of electrons - Abdrakhmetova, A. A.; Dauletbekova, A. K; Zhumazhanova, A.; Lisitsyna, L. A.; Korepanov, V. I. (Recent Contributions to Physics, 2013)
Spectral-kinetic characteristics of photo-and katodoluminescens were observed in the spectral range 3.7-1.6 eV of LiF crystals activated by oxygen: LiF-O, LiF-OH and -LiF-WO3 . We used pulsed spectrometry with nanosecond time resolution in the temperature range 15-300 K and the range of absorbed doses 1.6·101 -103 Gy. The temperature dependence of the efficiency of radiation to create molecular ions O2 - and the characteristic decay time of the long-lived and short-lived component of the pulsed cathodoluminescence in crystals LiF-OH, LiF-WO3 is investigated. For the study the optical absorption spectra in the spectral range of 1-6 eV and the transmission spectra of 0.1-0.5 eV is not irradiated and irradiated with electrons LiF-O, LiF-OH, LiF-WO3 crystals used Spectrophotometer SPh-256 and IR- Fourier spectrometer Nicolet 5700. Comparative analysis of the studied materials makes it possible to determine the influence of type of oxygen impurity in the lattice and related defects (polyvalent ion tungsten) on the luminescent characteristics of the material.